Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11121-016-0731-7
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with Adolescent Mother–Child Dyads and Cognitive Development in Early Childhood: a Meta-Analysis

Abstract: The cognitive development of children of adolescent mothers has often been considered to be at risk. The purpose of this meta-analysis is to examine whether early intervention could help foster more positive cognitive development in the 0- to 4-year-old children of adolescent mothers. Twenty-two studies were reviewed, involving 29 different intervention strategies and 3577 participants. An overall effect size (corrected for publication bias) of d = .24 was found (95% CI .11, .36). Intervention strategies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 73 publications
2
23
0
2
Order By: Relevance
“…Bakermans-Kranenburg et al (2003) demonstrated that shorter attachment interventions in early childhood produced significantly greater positive change in maternal interactive behavior and child attachment security than did longer interventions. Similarly, Baudry et al (2016) found that shorter interventions with adolescent mothers and their young children were linked to higher levels of child cognitive function. Such findings may be especially relevant for groups experiencing potential risk.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bakermans-Kranenburg et al (2003) demonstrated that shorter attachment interventions in early childhood produced significantly greater positive change in maternal interactive behavior and child attachment security than did longer interventions. Similarly, Baudry et al (2016) found that shorter interventions with adolescent mothers and their young children were linked to higher levels of child cognitive function. Such findings may be especially relevant for groups experiencing potential risk.…”
Section: Discussionmentioning
confidence: 93%
“…Intervention length may also have a moderating effect. Shorter interventions have been linked to greater improvements in parent and child outcomes (Bakermans-Kranenburg et al 2003;Baudry et al 2016;Pinquart and Teubert 2010); however, longer intervention strategies (i.e., the Nurse Family Partnership) are also effective (Olds 2006). Date of publication was assessed because, in contrast to in-person delivery, technology-assisted interventions may be more susceptible to changes across time, including increased technological capacity and accessibility (Jones 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have shown that with high-risk parents, most effective strategies for improving infant and early childhood cognitive outcome involve some level of interactive coaching, supporting basic theoretical postulates on the factors that drive early development (Sroufe et al, 2005). In a recent meta-analysis of 23 intervention studies concerned with the infant and early childhood cognitive outcome of the offspring of adolescent mothers, our group found effect sizes two to three times greater when specific interaction coaching strategies were part of intervention procedures than when intervention focused on other aspects of the developmental ecology (Baudry, Tarabulsy, Atkinson, Pearson, & St-Pierre, 2017). Moreover, interactive coaching has been successfully used with premature or otherwise biologically at-risk infants to improve the potential for child cognitive development (Field, Widmayer, Greenberg, & Stoller, 1982;Wallace & Rogers, 2010).…”
Section: Infant Developmentmentioning
confidence: 90%
“…Over the past ten years, Prevention Science alone has published thirty such reviews, including reviews on substance abuse prevention programs (Hennessy & Tanner-Smith, 2015), mental health interventions (Conley et al, 2015), and parenting interventions (Baudry et al, 2017).…”
Section: Meta-analysis With Robust Variance Estimation: Expanding Thementioning
confidence: 99%